Metode Ibn Adil Al-Hanbali (W 880h) Dalam Penghujahan Hadith Di Dalam Kitabnya Al-Lubab Fi Ulum Al-Kitab: Kajian Terhadap Surah Al-Fatihah - Ahmad Kamel Mohamed; Mohd Yakub @ Zulkifli Mohd Yusoff; Adel Abdul Aziz al-Ghiryani (USIM Press, 2024)
Volume : 3. No: 1 (page: 24-40)